Rapid physicochemical changes in the high Arctic Lake Kongressvatn caused by recent climate change - Holm, Trine Marianne; Koinig, Karin A.; Andersen, Tom; Donali, Espen; Hormes, Anne; Klaveness, Dag; Psenner, Roland (Aquatic Sciences, 2012)
High Arctic lakes are among the most sensitive ecosystems and climate change strongly affects their physical properties, especially water temperature, and mixing processes. To study the effect of recent climate change on such a lake in the Arctic environment, we measured water chemistry and temperature from 2005 to 2010 in Kongressvatn, a crenogenic meromictic lake in Spitsbergen (Svalbard). In addition, we monitored water column temperatures during two consecutive years and compared them to regional air temperature data and physicochemical lake data from 1962 and 1968, two relatively cold years. Summer surface water temperature was highly correlated to air temperature, and both have increased by approximately 2°C since 1962. Temperature monitoring during 2 years showed that the warm summer of 2007 resulted in increased water temperatures even in the stratified, denser hypolimnion. Our water chemistry measurements showed that the chemocline position in 2005-2010 was ca 12 m deeper than in 1962-1968, and a second, weaker, chemocline appeared at metalimnetic depths of 7-15 m. During the study period, the water level decreased by 4 m, and this change accelerated between 2008 and 2010. Our data support the hypothesis that water temperatures and stratification patterns are changing rapidly with air temperature, but changes in the catchment, such as glacial retreat and permafrost melting, may have an even stronger impact on lake properties.